Domestic Violence in The Perspective of Law and Human Rights - Melanie Pita Lestari; Zulkifli Ismail; Fransiska Novita Eleanora (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Domestic violence is more and more happening and increasing and sometimes experienced by women in the household so that they become victims. The perception of violence here is in the physical sense of the body and full of wounds or bruises. At the same time, psychologically, it is caused by fear due to the perpetrator's treatment of their mental State and violence due to sexual harassment in marriage or frequent sexual intercourse that is excessive than usual without seeing the partner's readiness. The problem studied is how the implications of domestic violence are viewed from the Law and human rights, especially for victims in fulfilling their rights. The purpose of this paper is to find out how domestic violence is related to Law and human rights. The method used is normative juridical research because it examines or examines from the literature or literature or laws and regulations relating to existing problems, where the result is that domestic violence is also a legal aspect and is also a violation of human rights related to it human rights, so that it is not only problems or domestic disputes, but the perpetrators can be punished for violating the rights of the victims themselves.